A new species of Prodistomum (Digenea, Lepocreadiidae) from Rastrelliger spp. (Scombridae) in the Gulf of Thailand - Gilardoni, Carmen; Ribas, Alexis; Suwannarat, Nannaphat; Poonlaphdecha, Srisupaph (My University, 2026)
A new species of Prodistomum (Digenea, Lepocreadiidae), Prodistomum chumphonense sp. nov., is described from the intestine of Rastrelliger kanagurta and Rastrelliger brachysoma (Scombridae) collected in the Gulf of Thailand. The new species is characterized by vitelline follicles confined to the hindbody but extending anteriorly to the level of the anterior to posterior margin of the ventral sucker; a ventral sucker consistently larger than the oral sucker; an esophageal region approximately equal in length to the prepharynx; an entire, oval ovary; and a tubular excretory vesicle terminating below the level of the intestinal bifurcation. The new species differs from most congeners, mainly those with vitelline follicles extending into the forebody, by the restriction of the vitellarium to the hindbody. Although morphometrically similar to some specimens in the literature previously identified as P. orientale, previous molecular phylogenetic analyses based on 18S, ITS2, and 28S rDNA sequences demonstrate that P. chumphonense sp. nov. represents a distinct taxon. The present study underscores the importance of integrating detailed morphometric with molecular data for accurate species delimitation in trematodes of the genus Prodistomum.
Keywords: Helminth; Indian mackerel; marine fish; parasite; Scombridae; short mackerel; Trematoda